'I was prepared to become infected as a frontline medical staff': A survey of Australian emergency department staff experiences during COVID‐19. (1st March 2022) - Scott, Anna Mae; Murray, Amanda; Jones, Mark; Keijzers, Gerben; Glasziou, Paul
Abstract: Objective: To identify challenges faced by Australian hospital healthcare staff during the COVID‐19 pandemic. Methods: We conducted an online survey (30 June–15 August 2020) of healthcare staff from Australian emergency and infectious disease departments. Participants were contacted via professional organisations and asked about preparedness, personal protective equipment (PPE), information flow, patient care, infection concerns, workload and mental health. We calculated the proportion of answers to yes/no and Likert‐style questions; free‐text responses were analysed thematically. Results: Respondents ( n  = 162) were 23–67 years old, 98% worked in EDs, 68% were female, 87% from Queensland, and most worked as nurses (46%) or specialists (31%). Respondents felt their workplace was prepared for the pandemic (79%), had sufficient information about PPE (83%); none were sent home because of PPE shortages. Eighty‐five percent received sufficient information from official bodies and 50% were aware of the National COVID‐19 Clinical Evidence Taskforce guidelines. Most (83%) had sufficient information to provide optimal patient care, but 24% experienced unfair/abusive patient behaviour. Most (76%) were concerned about becoming infected by patients, 67% about infecting patients, and 78% about infecting someone at home. Workload decreased for 82% but 42% looked after more patients. Fifty‐seven percent experienced additional work‐related stress: 60% reporting experiencing anxiety and 53% experiencing burnout, with 36% and 46% continuing to experience these, respectively. Key challenges included: emotional, workplace/organisational, family/loved ones and PPE factors. Conclusion: The Australian system provided sufficient information and PPE. Staff experienced considerable stress, infection concerns and emotional challenges, which merit consideration in preparing for the future. Abstract : We surveyed Australian hospital healthcare staff during the second wave of the COVID‐19 pandemic. Majority felt they had sufficient information and amounts of PPE and knew enough to provide optimal care to patients. However, many reported concerns about becoming infected with and transmitting COVID‐19, half suffered from additional stress, and many continue to experience burnout and anxiety.